Endotelioand cardioprotective effects of HMG-Co-A reductase in endotoksininducing endotelial dysfunction - T. A. Denisuk; M. V. Pokrovskii; O. V. Philippova; O. S. Gudyrev; T. G. Pokrovskaya; M. V. Korokin; O. A. Osipova (Кубанский научный медицинский вестник)
The use of inhibitors of HMG-Co-A reductase inhibitor simvastatin, atorvastatin, rosuvastatin and nanoparticulative rosuvastatin on background modeling endotoksininducing pathology, introduction of strain 603 Staphylococcusaureus leads to the development of dose-response endotelioprotectiv action, expressed in the normalization of QED, prevent increase adrenoreactivity and exhaustion of myocardial reserve and and normalization of biochemical markers of inflammation (C-reactive protein) and the level of proinflammatory cytokines. When this is detected positive dynamics and-products of NO and expression of eNOS.